2021
DOI: 10.3390/membranes11010030
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Power during Veno-Venous Extracorporeal Membrane Oxygenation Initiation: A Pilot-Study

Abstract: Mechanical power (MP) represents a useful parameter to describe and quantify the forces applied to the lungs during mechanical ventilation (MV). In this multi-center, prospective, observational study, we analyzed MP variations following MV adjustments after veno-venous extra-corporeal membrane oxygenation (VV ECMO) initiation. We also investigated whether the MV parameters (including MP) in the early phases of VV ECMO run may be related to the intensive care unit (ICU) mortality. Thirty-five patients with seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Only a few studies addressed this issue, with conflicting results. While Chiu et al reported a significant association between MP in the early phase of ECMO and mortality [ 50 ], Belliato et al [ 51 ] and Schmidt et al [ 21 ], did not report such an association. Therefore, it is possible that under VV-ECMO, DP may be more discriminant than MP to track ongoing VILI.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies addressed this issue, with conflicting results. While Chiu et al reported a significant association between MP in the early phase of ECMO and mortality [ 50 ], Belliato et al [ 51 ] and Schmidt et al [ 21 ], did not report such an association. Therefore, it is possible that under VV-ECMO, DP may be more discriminant than MP to track ongoing VILI.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the clinical implications of MP were currently all observational. Some studies showed a good correlation between MP and mortality [ 21 , 22 ], whereas some did not [ 23 , 24 ]. Still, some studies barely established a correlation by modifying the definition of MP calculated [ 4 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher mechanical power while on VV‐ECMO has been demonstrated to be associated with a higher 30‐day and in‐hospital mortality as well as lower 60‐day ventilator‐free days [54, 58]. Another study did not demonstrate any association between mechanical power and ICU survival [59], but this study was limited by a small sample size and may not have been appropriately powered to detect an effect [59]. Future studies investigating mechanical power during VV‐ECMO should perhaps be enriched with patients whose lungs are being ventilated with the aforementioned settings to better elucidate the relationship between mechanical power and outcomes in ARDS patients receiving VV‐ECMO.…”
Section: Mechanical Powermentioning
confidence: 99%